1994
DOI: 10.3109/00016349409029404
|View full text |Cite
|
Sign up to set email alerts
|

Societal costs of antenatal and obstetrical care

Abstract: Perinatal health care is an important part of a nation's health care system. In the Nordic countries this type of health care is provided by the national public health systems without cost for the women. The societal costs of the care provided have, however, not been known. The aim of the present study was to estimate societal costs of antenatal and obstetrical care in a Norwegian county during a twelve month period 1988-89. A total of 1908 women delivered during the registration period. The mean total cost wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The UK study by Long & Sprigg (1998) 10 found costs very similar to ours. The reported costs from the two Scandinavian studies were somewhat higher 11,12 .…”
Section: Sensitivity Analysesmentioning
confidence: 96%
See 1 more Smart Citation
“…The UK study by Long & Sprigg (1998) 10 found costs very similar to ours. The reported costs from the two Scandinavian studies were somewhat higher 11,12 .…”
Section: Sensitivity Analysesmentioning
confidence: 96%
“…This was at least partly due to the duration of scans being greater in Helsinki. The Norwegian study 12 was a more general study of costs of antenatal and obstetric care. It was not clear what had been included in the cost of a scan but it was very similar to the Finnish figure.…”
Section: Discussionmentioning
confidence: 99%
“…This was much higher than the cost of any of the routine scans estimated in the costing study we carried out at Liverpool, which averaged between £14 and £16, depending on the purpose of the scan. Only three studies, however, presented data for the cost of ultrasound 10,11,20 . The average cost of a scan in these three studies was £35.42.…”
Section: Discussionmentioning
confidence: 99%
“…of equipment), and others are average costs per woman tested. Two studies 10,20 also considered the woman's travel costs. At UK prices in 1997 these averaged between £1.43 and £16.65.…”
Section: Studiesmentioning
confidence: 99%
“…The relative cost-effectiveness of the two programmes of antenatal care may change considerably when women's costs are included, as has been shown elsewhere. 20,21 This leads us to ask whose viewpoint the analysis should represent. While it is important for an economic evaluation to adopt a societal perspective in order to illustrate where the most benefit could be gained, the costs of different agencies should also be presented separately, as they may highlight conflicts in incentive to change practice.…”
Section: What Is the Question?mentioning
confidence: 99%